The Role of Parents in Stimulating the Language Development of Children Aged 3-5 Years: A Phenomenological Study - Sri Mahartini, Gusti Ayu (Sekolah Tinggi Agama Islam Kuningan, 2025)
Parental involvement plays a critical role in early childhood language development, yet limited research has explored the lived experiences of parents as language facilitators during the preschool years. This phenomenological study aimed to explore and describe the essential structures of parental experiences in stimulating language development among children aged three to five years. Sixteen parents of typically developing preschool-aged children participated in in-depth semi-structured interviews. Data were analyzed using Colaizzi's phenomenological method, involving systematic extraction of significant statements, formulation of meanings, theme clustering, and synthesis of essential structures. Five major themes emerged: (1) Constructing Identity as Language Facilitator parents' transformation from intuitive to intentional facilitation; (2) Weaving Language Into Daily Life integration of language stimulation strategies within authentic family routines including shared reading, mealtime conversations, play-based interactions, and environmental print experiences; (3) Navigating Challenges and Uncertainty confronting barriers including time constraints, resource limitations, knowledge gaps, and child-related challenges while developing adaptive responses; (4) Emotional Dimensions and Relational Rewards experiencing joy, pride, anxiety, guilt, and profound relational satisfaction through language-rich interactions; and (5) Sociocultural Contexts and Community Influences shaping beliefs and practices through cultural backgrounds, educational partnerships, community resources, and broader social discourses. Parental language facilitation encompasses complex identity construction, emotional labor, adaptive problem-solving, and meaning-making processes deeply embedded in sociocultural contexts. Findings inform development of strengths-based, culturally responsive interventions that honor diverse family circumstances while supporting optimal language learning environments.